A Digitally Controlled D-Band Phase Shifter for FMCW Radar and RadCom in SiGe BiCMOS - Schrotz, Albert-Marcel; Breun, Sascha; Schonharl, Stefan; Weigel, Robert (2024 IEEE Wireless and Microwave Technology Conference, WAMICON 2024, 2024)
This paper presents an integrated vector modulator-based phase shifter operating in the frequency range of 140 GHz to 170GHz (D-band). A 360° phase and amplitude control is realized by four 7-bit SPI-controllable current sources controlling the I and Q branches of the vector modulator. Measurements at a phase resolution of 11.25° show a gain of 5.4 dB with an RMS phase error of < 1.80° and remarkable < 1.0° in the range of 150GHz to 170 GHz. It shows an RMS amplitude error of < 3.4 dB (< 1.9 dB from 144 GHz to 170 GHz). This phase shifter is suitable, e.g., for Doppler multiplexing in FMCW radar or modulation of communication signals for RadCom applications. The circuit is manufactured using Infineon's 130nm B11HFC BiCMOS (ft/fmax of 250GHz/370GHz) technology. The die area is 0.111mm2 (with I/Q generation), and the maximum power consumption is 151mW.
CRIS-Team Scopus Importer:2024-05-31
Keywords: BiCMOS integrated circuits; D-band; millimeter-wave integrated circuits; phase shifter; vector modulator (VM)